PCLO Is Associated with Tumor Mutational Burden and Immunity in Patients with Oral Squamous Cell Carcinoma - Yuping Liu; Ye Zhang; Lijing Zhu; Zheng Zhou; Yajuan Cui; Heyu Zhang; Chuanxiang Zhou (Current Issues in Molecular Biology)
To determine predictive biomarkers for prognosis by analyzing the association between tumor mutational burden (TMB) and mutant genes in patients with oral squamous cell carcinoma (OSCC) and to validate PCLO as an OSCC predictive biomarker, OSCC genetic mutation data were downloaded from The Cancer Genome Atlas (TCGA) and the International Cancer Genome Consortium (ICGC) database. Immune cell infiltration analysis and visualization were performed using R software. The relationships between overall survival (OS) and mutant genes or clinicopathological factors were investigated by Kaplan–Meier analysis and Cox regression analysis, respectively. Gene set enrichment analysis (GSEA) was used to explore the associations between mutant genes and functional pathways. Immunohistochemistry was performed to verify the presence of the piccolo protein in OSCC tissues. Finally, 17 mutated genes shared between TCGA and the ICGC database were detected. The TMB in the PCLO-mutated group was found to be significantly greater than that in the PCLO wild-type group, and PCLO mutation was associated with poor OS. Cox regression analysis revealed that PCLO is a significant prognostic factor for OSCC. GSEA and immune cell infiltration analysis revealed that PCLO is associated with the immune system, which suggests that PCLO mutation might affect the immune response. PCLO expression was considerably higher in OSCC tissues with PCLO mutations than in corresponding normal epithelium tissues and OSCC tissues without PCLO mutations (p < 0.05). PCLO mutation could serve as a promising predictive biomarker for prognosis in patients with OSCC.